Biology of red scale insect, Aonidiella aurantii and its biological control using Beauveria bassiana and Metarhizium anisopliae - Anang Triwiratno,; Susi Wuryantini,; Agus Sugiyatno,; Sudarminto Setyo Yuwono,; Faiqotul Jannah,; Arrohmatus Syafaqoh Li’aini,; Joko Purnomo,; Cinta Badia Ginting, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In many regions, including Indonesia, red-scale insect, Aonidiella aurantii Maskell (Hemiptera: Diaspididae) is regarded as a major citrus pest. To reduce the negative impact of pests on citrus production, innovative techniques based on entomopathogenic fungi (EPF) might be an effective alternative for controlling A. aurantii. This work aimed to investigate the biology of A. aurantii, find the most effective phase for applying EPF, and test the pathogenicity of Beauveria bassiana and Metarhizium anisopliae toward A. aurantii. Single application and combining these two EPFs at 106 and 107 conidia mL-1 were assayed. It was found that EPFs should be applied to the first instar of A. aurantii before the wax layer develops to improve its penetration capacity. As a result, EPF concentration influences the mortality rate of A. aurantii. M. anisopliae (52.0 and 95.0%) caused more mortality in A. aurantii compared to B. bassiana (60.0 and 72.5%) 106 and 107 conidia mL-1 , respectively. The pathogenicity of M. anisopliae itself is even equivalent to the pathogenicity caused by their consortium. This research concluded that, under laboratory study, A. aurantii was effectively controlled by B. bassiana and M. anisopliae.